Staphylococcus lugdunensis in children: A retrospective analysis - Thomas Patrick Bowman; Ashutosh Deshpande; Alison Balfour; Kathleen Harvey‐Wood (Wiley, 2022)
ABSTRACT Importance Staphylococcus lugdunensis (S. lugdunensis) is a coagulase‐negative staphylococcus (CoNS), found commonly as skin flora in humans. While most species of CoNS are clinically benign, S. lugdunensis can exhibit a similar virulence to that of S. aureus. However, there is scant data concerning S. lugdunensis infection in the pediatric population. Objective To ascertain local S. lugdunensis infection rates and sensitivity patterns in the pediatric population. Methods A retrospective analysis was undertaken of all S. lugdunensis isolates across a 6‐year period from 2015 to 2020. Data were collected from electronic patient notes and laboratory records. Matrix‐assisted laser desorption ionization and time of flight mass spectrometry were used to identify isolates. Results Ninety‐six isolates of S. lugdunensis were identified from 86 patients. Of these, 34 isolates were treated as an infection. Twenty‐three (67.6%) were found to have skin as the primary source of infection. While the observed number was small, central nervous system (CNS) sources of S. lugdunensis infection appear to be a significant source: all three isolates cultured from cerebrospinal fluid were clinically managed as infection. All three were associated with ventriculoperitoneal (VP) shunt infection. No cases of S. lugdunensis infective endocarditis were identified. About 18.6% of S. lugdunensis isolates were resistant to flucloxacillin. Interpretation S. lugdunensis is an uncommon but significant cause of infection in the pediatric population and appears to be a rising cause of CNS infection, particularly when associated with VP shunts. Flucloxacillin is recommended locally as the first choice of antibiotic.